Examination of chaotic behaviours using bond graph model - Gülten, A; Türk, M (Pergamon-Elsevier Science Ltd, 2003)
In this paper, modelling and simulation of Chua's chaotic oscillator, which exhibits rich chaotic behaviours, are presented by using the bond graph model. Up to now modelling of Chua's chaotic oscillator using bond graph model is not yet developed. The non-linear resistor in the circuit is modelled in this contribution by linear time-invariant components and ideal switches using piecewise linearization approach. The bond graph model of all the circuit including switches is then generated. Simulations are provided via the computer program called as BOMAS using the obtained bond graph model. Finally, Chua's circuit is verified experimentally. It is shown that all experimental and simulation results well agree with the chaotic behaviours of Chua's circuit. (C) 2003 The Franklin Institute, Published by Elsevier Ltd. All rights reserved.
Keywords: chaos; Chua's circuit; bond graph model; switched circuits; piecewise linearization